CYP3A4*1G gene Polymorphism on Javanese People - Em Sutrisna; Iwan Dwiprahasto; Erna Kristin (Universitas Gadjah Mada, 2011)
Most of drugs are metabolized by cytochrome P 450 (CYP) enzyme. Cytochrome P450 3A4 is thecytochrome that is involved in metabolizing more than 60% of all medicine used in human. The variationof this CYP3A4 gene will affect the catalytic activity of this enzyme. Recently, CYP3A4*1G in intron 10 wasfound in Chinese and Japanese population. There is a substitution of G to A at position 82266 in intron 10. Thepurpose of this research was to investigate the frequency of allele and genotype CYP3A4*1G. Samples weretaken from bloods of the subjects of the research. The examination of CYP3A4*1G was conducted by RTLP-PCRmethod.As the results of this research, the frequency of CYP3A4*1G in Javanese people is CYP3A4*1/*1 0.25,CYP3A4*1/*1G 0.55 and CYP3A4*1G/*1G 0.20. Frequency of allele G: 0.53, allele A: 0.47. The Fisher’s exact- testshows that the allele and genotype frequencyis p. 1.000. The allele and genotype frequency of Javanese peopleisstill in Hardy-Weinberg equilibrium.